2021
DOI: 10.1111/jcpt.13474
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin area under the curves estimated with pharmacokinetic equations using trough‐only data

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…We also observed that the AUC 24 estimates from the VancoPK single‐concentration calculator had less bias and lower imprecision when compared to the ClinCalc single‐concentration calculator. Fewel performed a retrospective study assessing the accuracy and precision of AUC 24 estimates from the VancoPK single‐concentration vancomycin calculator versus the 2PK reference method 8 . This study found a mean AUC 24 difference of 1.6 mg*h/L between the 2PK reference method and the VancoPK single‐concentration vancomycin calculator.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also observed that the AUC 24 estimates from the VancoPK single‐concentration calculator had less bias and lower imprecision when compared to the ClinCalc single‐concentration calculator. Fewel performed a retrospective study assessing the accuracy and precision of AUC 24 estimates from the VancoPK single‐concentration vancomycin calculator versus the 2PK reference method 8 . This study found a mean AUC 24 difference of 1.6 mg*h/L between the 2PK reference method and the VancoPK single‐concentration vancomycin calculator.…”
Section: Resultsmentioning
confidence: 99%
“…ClinCalc utilizes Bayesian modelling to estimate vancomycin clearance (CL v ) and volume of distribution ( V d ) 6 . VancoPK calculates patient‐specific V d , elimination rate ( K e ), CL v , and AUC from the data utilizing first‐order, intermittent IV infusion equations 7,8 . Although these online calculators are likely easier to utilize in comparison to the guideline‐recommended methods, their accuracy for estimating AUC 24 is uncertain.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…Using an internally validated online calculator called vancopk.com, patient age, height, weight, serum creatinine and sex were used to initially predict each patient's population‐based PK data and associated vancomycin dosing regimens 12 12 .…”
Section: Methodsmentioning
confidence: 99%
“…Using an internally validated online calculator called vancopk.com, patient age, height, weight, serum creatinine and sex were used to initially predict each patient's population-based PK data and associated vancomycin dosing regimens. 12 The initial dosing calculator uses creatinine clearance to estimate vancomycin clearance and uses other population-based equations to estimate various PK parameters, such as Ke. 12 Predictions were made based on the following calculator settings: infusion rate of 1000 mg/h, goal trough range of 10-15 mg/L and vancomycin MIC of 1 mg/L against S. aureus.…”
Section: Pharmacokinetic Datamentioning
confidence: 99%
See 1 more Smart Citation